(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The problem of studying emotional and communicative competence has received wide recognition in medical education and in the interdisciplinary field. Numerous studies have been conducted in medical education to explore the role of emotional and communicative competence in patient care, and to develop training programs to enhance these competencies among medical students and healthcare professionals.